Diversity of insect in Gua Gunung Senyum, Pahang / Nor Fatihah Ghozali - Ghozali, Nor Fatihah (2016)
Cave is a natural opening in rocky mountain that can be entered by human or other living organism. Animals that live in the cave are ranging from tiny microscopic invertebrates such as cricket and flies to large organism such as snakes, and bats. One of the common organisms in caves is insect. There are a lot of data recorded about the insect around the world, but record data for insects in the cave is still not properly described. With data record, the diversity of insect that present inside cave can also be compared with the diversity of insect living outside of a cave. Objectives of this study are to identify the diversity of insects that are present in the cave and to compare the diversity of insect in different zones based on light intensity of Gua Gunung Senyum, Pahang. For cave sampling, four types of trap which are pit fall trap, light trap, impact trap and sticky trap were used. Pitfall trap were place in transect form and the other three traps is placed randomly in three different zone which are entrance zone, middle zone and dark zone respectively. The zones are classified base on the light intensity in the cave. As the result, there are 2292 individuals of insect were collected from three different zone. Entrance zone represents the highest abundance from the total collection which is 61%, while middle zone show the lowest abundance with 6% and dark zone represents 33%. Formicidae have been recorded as the most abundant family with 1310 number of individuals in total, which mostly abundant in entrance zone with 1264 individuals, while 40 individual in middle zone and 6 individual in dark zone. Family Simuliidae is the most abundant insect in middle zone with 54 individual. The most abundant insect present in dark zone is Ripiphoridae from order Coleoptera with total number individual is 589. In futher study, identification until the species level can be done to know that the value and inventory more accurate. From the composition of insects species in three different zone, the diversity of insect will be known more accurate.